2007
DOI: 10.3346/jkms.2007.22.6.973
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the Association between HLA-DRB1 Allele and Rheumatoid Arthritis Susceptibility in Asian Populations

Abstract: The aims of this study were to summarize results on the association of HLA-DRB1 with rheumatoid arthritis (RA) in Asians and to determine if the shared epitope (SE) hypothesis could explain the meta-analysis results. Among the papers published between January 1987 and July 2006 on RA susceptibility in Asian-Mongoloid populations (Korean, Japanese, Chinese, and Thai), 12 were selected for the meta-analysis. Mongoloid-Asian patients with RA had significantly higher frequencies of HLA-DRB1*0101, *0401, *0410, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
30
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 35 publications
(37 reference statements)
9
30
3
Order By: Relevance
“…Other studies demonstrated association between these alleles and RA; they have recently been reviewed in a number of meta-analyses or review articles 1112. Consistent with the above results, we found DRB1*10 to be a predisposing factor in the studied population; however, in contrast, DRB1*01 allele was found to be equally distributed between RA and control groups.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Other studies demonstrated association between these alleles and RA; they have recently been reviewed in a number of meta-analyses or review articles 1112. Consistent with the above results, we found DRB1*10 to be a predisposing factor in the studied population; however, in contrast, DRB1*01 allele was found to be equally distributed between RA and control groups.…”
Section: Discussionsupporting
confidence: 90%
“…Another meta-analysis, in Asian-Mongoloids (Korean, Japanese, Chinese and Thai), showed that HLA-DRB1*0101, *0401, *0405, *0410 and *1001 are contributory to susceptibility, while HLA-DRB1* 0301, *0403, *0406, *0701, *1301 and *1405 are protective 11. Like the results among Asian populations, the HLA-DRB1*03 was found in our study to play a protective role against RA.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in accordance with studies performed by Diane van der Woude [6] and Kyung Ran Jun [30]. Previous study has…”
Section: Discussionsupporting
confidence: 83%
“…In a meta-analysis on the Asian population, the DRB1*0403, DRB1*0701, DRB1*1101 and DRB1*1405 subtypes were found as the protective alleles in patients with RA (17). In addition, in another study on RA patients in Korea, DRB1*0701 has been described as the protective subtype (7).…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis on the Asian population, the DRB1*1001 allele was shown to be more frequent in patients with RA compared to controls (17). In the Spanish (13) and Greek populations (14), the DRB1*1001 allele was found to be related with the predisposition to RA.…”
Section: Discussionmentioning
confidence: 99%